2002
DOI: 10.1677/joe.0.1750637
|View full text |Cite
|
Sign up to set email alerts
|

Proinsulin processing in the diabetic Goto-Kakizaki rat

Abstract: The biosynthesis and processing of proinsulin was investigated in the diabetic Goto-Kakizaki (GK) rat. Immunofluorescence microscopy comparing GK and Wistar control rat pancreata revealed marked changes in the distribution of -cells and pronounced -cell heterogeneity in the expression patterns of insulin, prohormone convertases PC1, PC2, carboxypeptidase E (CPE) and the PC-binding proteins 7B2 and ProSAAS. Western blot analyses of isolated islets revealed little difference in PC1 and CPE expression but PC2 imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 66 publications
(60 reference statements)
3
29
0
Order By: Relevance
“…It should be noted that GK ␤-cells were not depleted of insulin as compared with ␤-cells of the control Wistar rat (data not shown); indeed, other studies also revealed no deficiency in insulin synthesis or storage in the GK rat (36). Furthermore, the degree of expression of PKC␣ was reduced in the GK ␤-cell, confirmed both histochemically and by Western blot analysis.…”
Section: Dynamics Of Glucose-induced Pkc Localizationsupporting
confidence: 53%
See 2 more Smart Citations
“…It should be noted that GK ␤-cells were not depleted of insulin as compared with ␤-cells of the control Wistar rat (data not shown); indeed, other studies also revealed no deficiency in insulin synthesis or storage in the GK rat (36). Furthermore, the degree of expression of PKC␣ was reduced in the GK ␤-cell, confirmed both histochemically and by Western blot analysis.…”
Section: Dynamics Of Glucose-induced Pkc Localizationsupporting
confidence: 53%
“…Nagamatsu et al (15) as well as Gaisano et al (48) demonstrated reduced levels of key components of the SNARE system, an important part of the distal exocytotic complex. While Guest et al (36) reported an intact insulin biosynthetic machinery and unaltered insulin content in GK ␤-cells, Nagamatsu's studies (15) pointed toward increased rate of insulin degradation and diminished insulin stores. Thus, diminished translocation of PKC into GK ␤-cell nuclei could be related to the impaired activation of one or more genes involved in production of the SNARE proteins, while the failure of PKCε to relocalize may reflect a disturbed step in trafficking of insulin granules toward the exocytotic site.…”
Section: Dynamics Of Glucose-induced Pkc Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This antiserum recognizes the various proSAAS truncated forms described below by both Western blotting as well as by ELISA, and exhibits 30% cross-reactivity with frog proSAAS (22). Antiserum LS45 has been previously used to demonstrate proSAAS immunoreactivity in pancreatic islets (71) and brains from patients with Alzheimer's disease (29). Deidentified human tissues were procured from the NIH NeuroBioBank.…”
Section: Methodsmentioning
confidence: 99%
“…This enhanced ratio could depend on changes in expression or activity of the prohormone convertases (28). Islet PC2 expression in the diabetic Goto-Kakizaki rat is markedly reduced relative to the PC2 levels in the nondiabetic Wistar rat (29). This decrease does not result in elevated levels of proinsulin or proinsulin processing intermediates.…”
mentioning
confidence: 95%